2003
DOI: 10.1210/jc.2002-021304
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Transport and Phosphorylation in Skeletal Muscle in Obesity: Insight from a Muscle-Specific Positron Emission Tomography Model

Abstract: A controversial area in understanding the contribution of obesity to skeletal muscle insulin resistance is the distribution of control of glucose metabolism across proximal steps of glucose delivery, trans-membrane transport, and intracellular trapping via phosphorylation. Dynamic positron emission tomography (PET) imaging of skeletal muscle [(18)F]2-deoxy-2-D-glucose ((18)F-FDG) uptake provides an in vivo method for assessment of these steps in humans. In the current study we have examined the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 26 publications
4
51
0
Order By: Relevance
“…The aims of this study were to evaluate the effectiveness of a standardized insulin protocol in reducing glycemia, review 18 F-FDG biodistribution with such a protocol, and assess its clinical impact. Methods: Sixty-three patients with glycemia greater than 10 mmol/L received insulin doses intravenously according to a standardized protocol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aims of this study were to evaluate the effectiveness of a standardized insulin protocol in reducing glycemia, review 18 F-FDG biodistribution with such a protocol, and assess its clinical impact. Methods: Sixty-three patients with glycemia greater than 10 mmol/L received insulin doses intravenously according to a standardized protocol.…”
mentioning
confidence: 99%
“…One hundred six consecutive euglycemic patients (,6.2 mmol/L) served as controls. 18 F-FDG biodistribution was evaluated by 2 experienced PET readers on a 5-point visual scale based on muscular uptake. The 63 patients who received insulin were divided into insulin subgroup A, with adequate biodistribution (score 0, 1, or 2) and insulin subgroup B, with altered biodistribution (score 3 or 4).…”
mentioning
confidence: 99%
“…In a follow-up publication (66), using similar methodology, the same group reported a normal rate constant for glucose transport in obese individuals but a decreased rate constant for glucose phosphorylation. In subsequent publications (67,68), the investigators used a muscle-specific compartmental model and demonstrated a reduction in the insulin-stimulated glucose transport parameter in obese nondiabetic subjects vs. obese T2DM subjects. Since a lean T2DM group was not studied (67,68), it is difficult to discern whether T2DM or obesity was responsible for the reported defects in glucose transport and glucose phosphorylation.…”
Section: D-mannitol/3-o-methyl-d-[ 14 C]glucose/d-[3-mentioning
confidence: 99%
“…In subsequent publications (67,68), the investigators used a muscle-specific compartmental model and demonstrated a reduction in the insulin-stimulated glucose transport parameter in obese nondiabetic subjects vs. obese T2DM subjects. Since a lean T2DM group was not studied (67,68), it is difficult to discern whether T2DM or obesity was responsible for the reported defects in glucose transport and glucose phosphorylation. Moreover, there was a marked difference in the severity of insulin resistance in the obese nondiabetic groups in these two studies (67,68).…”
Section: D-mannitol/3-o-methyl-d-[ 14 C]glucose/d-[3-mentioning
confidence: 99%
See 1 more Smart Citation